Influence of carbonate intercalation in the surface-charging behavior of Zn-Cr layered double hydroxides - Rojas Delgado, Ricardo (2010)
The influence of interlayer composition in the surface charge and reactivity of layered double hydroxides (LDHs) has been explored. With this purpose, a chloride-intercalated Zn-Cr-LDH has been synthesized by the constant pH coprecipitation method and afterwards exchanged with carbonate to obtain solids with different Cl-/CO32- ratios. The solids structure has been characterized by elemental chemical analysis, powder X-ray diffraction and infrared spectroscopy, while its surface-charging behavior and reactivity have been studied by acid-base potentiometric titrations and electrophoretic mobility determinations. The chloride-intercalated sample shows an increasing hydroxyl adsorption with increasing pH and decreasing support electrolyte concentration and the particles present positive electrophoretic mobility in the measured pH range. As carbonate content increases in the samples, the total OH- uptake diminishes and the samples show an isoelectric point at pH around 10. When the gallery is totally occupied by carbonate anions, the OH uptake vs. pH curves registered at different electrolyte concentrations merge at around pH 10. A LDH-water interface model has been used to give an interpretation to the experimental data. The model indicates that as carbonate content increases, the sample behavior becomes similar to that of a metal (hydr)oxide and that surface (bi)carbonate anions undergo acid-base reactions. © 2009 Elsevier B.V. All rights reserved.